AMPK Dilates Resistance Arteries via Activation of SERCA and BKCa Channels in Smooth Muscle. Issue 1 (July 2015) - Schneider, Holger; Schubert, Kai Michael; Blodow, Stephanie; Kreutz, Claus-Peter; Erdogmus, Serap; Wiedenmann, Margarethe; Qiu, Jiehua; Fey, Theres; Ruth, Peter; Lubomirov, Lubomir T.; Pfitzer, Gabriele; Mederos y Schnitzler, Michael; et al.
<x xml:space="preserve">Abstract</x> The protective effects of 5′-AMP–activated protein kinase (AMPK) on the metabolic syndrome may include direct effects on resistance artery vasomotor function. However, the precise actions of AMPK on microvessels and their potential interaction are largely unknown. Thus, we set to determine the effects of AMPK activation on vascular smooth muscle tone and the underlying mechanisms. Resistance arteries isolated from hamster and mouse exhibited a pronounced endothelium-independent dilation on direct pharmacological AMPK activation by 2 structurally unrelated compounds (PT1 and A769662). The dilation was associated with a decrease of intracellular-free calcium [Ca2+]i in vascular smooth muscle cell. AMPK stimulation induced activation of BKCa channels as assessed by patch clamp studies in freshly isolated hamster vascular smooth muscle cell and confirmed by direct proof of membrane hyperpolarization in intact arteries. The BKCa channel blocker iberiotoxin abolished the hyperpolarization but only partially reduced the dilation and did not affect the decrease of [Ca2+]i. By contrast, the sarcoplasmic/endoplasmic Ca2+-ATPase (SERCA) inhibitor thapsigargin largely reduced these effects, whereas combined inhibition of SERCA and BKCa channels virtually abolished them. AMPK stimulation significantly increased the phosphorylation of the SERCA modulator phospholamban at the regulatory T17 site. Stimulation of smooth muscle AMPK represents a new, potent vasodilator mechanism in resistance vessels. AMPK directly relaxes vascular smooth muscle cell by a decrease of [Ca2+]i. This is achieved by calcium sequestration via SERCA activation, as well as activation of BKCa channels. There is in part a mutual compensation of both calcium-lowering mechanisms. However, SERCA activation which involves an AMPK-dependent phosphorylation of phospholamban is the predominant mechanism in resistance vessels.